Measuring the level of unemployment in Iraq by using the user / product schedule for 2010 - كامل مصطفى; محسن منتهى زهير (Journal of Economics and Administrative Sciences, 2017)
Economic performance is one of the most important indicators of economic activity and with the performance of the economy progress varied sources of output and increase economic growth rates and per capita national income, and to recover the business environment and increase investment rates and rising effectiveness of the financial and monetary institutions and credit market. Which leads to increased employment rates and reducing unemployment rates and the elimination of many of the social problems and improve the average per capita income as well as improve the level of national income. The input / output tables is a technique mathematical indicates economic performance and which shows the extent of contribution and interaction and mutual harmony between national sectors of the economy, it is through inference parameters economic sectors can come to know the strength of forward linkages and the background to those sectors. Which enhances the ability of each economic sector in the provision of production inputs to other sectors on the one hand, and how the sector can use the output of other sectors in economic activity fed by the other hand. The problem of unemployment linked to output via the labor market, and the provision of economic resources, expertise and skills acquired labor force in the production process. This study was based on the user / product tables to get to the actual level of unemployment in the economy in terms of GNP. Which helps the decision maker to recognize that the real amount of unemployment and make the necessary treatments to eliminate that level of unemployment through activation of the role output across sectors.